(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This novel describes the adolescent awakening of two sisters named Lalitha and Saroja, belonging to a lower middle class family of a south Indian village. The problem that Markandaya has taken is—the struggle between urban and non-urban elements of life, between pre and post independence, between old and new, between traditional eastern and modern western ways. It was the challenge before post-independence India to consolidate and preserve the new form of society that still was in the grip of poverty, ignorance and backwardness. People had to work hard to make India free of all these evils. However, those who took participation in the movement for freedom, not an insignificant number, though at the lower cadre, belonged to India’s villages.